Georgia : Report on Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2013)
This report is on the observance of standards and codes for the FATF 40 recommendations for antimoney laundering (AML) and special recommendations on combating the financing of terrorism. The government of Georgia indicated that the recommendations of the report have already been put into an action plan to implement appropriate corrective measures. Executive Directors approve that the regime has significantly improved since the last assessment. However, weaknesses with regard to compliance with key elements of the standard should be urgently addressed in light of significant vulnerabilities and threats.